Archaea and Bacteria Exposure in Danish Livestock Farmers. Issue 9 (28th August 2019) - Bønløkke, Jakob Hjort; Duchaine, Caroline; Schlünssen, Vivi; Sigsgaard, Torben; Veillette, Marc; Basinas, Ioannis
Abstract: Objectives: Methanogenic archaea have been found to make up part of the bioaerosols in pig, cattle, and poultry farms. So far no attempts have been made to determine how season, farm type, and farm characteristics may affect workers' exposure to archaea. Methods: Personal filter samples from 327 farmers working on 89 Danish farms were analysed for the number of 16S rRNA gene copies from archaea and bacteria and for their dust and endotoxin content. The farms were visited during summer and winter. Information on farm type and stable characteristics were collected using self-reported activity diaries and walk-through surveys. Differences in archaea and bacteria levels with farm type and stable characteristics and correlations with dust and endotoxin levels were examined. Results: Personal archaea exposure was documented in all farm types including, for the first time, during mink farming. At 7.3*10 4 gene copies m −3 the archaea levels were around two orders of magnitude lower than bacteria levels at 5.7*10 6 gene copies m −3 . At 1.7*10 5 gene copies m −3 among pig farmers and 1.9*10 4 gene copies m −3 among cattle farmers the archaea levels differed with farm type ( P < 0.0005). The archaea and bacteria levels correlated weakly with a Pearson correlation coefficient of 0.17. Neither archaea nor bacteria levels differed by season. In pig farms the archaea levels differed by type of ventilation and by wetness of the floor. Conclusions: Archaea levels were not neglible and appeared to vary greatly between farm types. In pig farms they varied with some farm characteristics. Archaea levels appeared to depend on factors that differed from those of bacteria.